Sequential Role of SOXB2 Factors in GABAergic Neuron Specification of the Dorsal Midbrain - Makrides, Neoklis; Panayiotou, Elena; Fanis, Pavlos; Karaiskos, Christos; Lapathitis, George; Malas, Stavros (Frontiers in Molecular Neuroscience, 2018)
Studies proposed a model for embryonic neurogenesis where the expression levels of SOXB2 and SOXB1 regulate the differentiation status of the neural stem cells. However, the precise role of the SOXB2 genes remains controversial. Therefore, this study aims to investigate the effects of individual deletions of the SOX21 and SOX14 genes during the development of the dorsal midbrain. In this study SOX21 and SOX14 have been shown to function distinctly towards the commitment of specific neuronal lineages. More explicitly, deletion of SOX21 reduced the expression of the GABAergic precursor marker GATA3 and BHLHB5 while the expression of GAD6, which marks GABAergic terminal differentiation, was not affected. In contrast deletion of SOX14 alone was sufficient to inhibit terminal differentiation of the dorsal midbrain GABAergic neurons. Furthermore, we demonstrate through gain-of-function experiments, that despite the homology of SOX21 and SOX14, they have unique gene targets and cannot compensate for the loss of each other. Taken together, these data do not support a pan-neurogenic function for SOXB2 genes but instead that they influence the specification of distinct neuronal lineages.